Breastfeeding Experiences of Autistic Women. Issue 1 (January 2022) - Wilson, Jane C.; Andrassy, Bri
Abstract: Purpose: The purpose of this study was to explore the experiences of autistic women who breastfed. Study Design and Methods: We used a qualitative phenomenology design and a thematic analysis method. Semistructured interviews were conducted using a purposive sample from social media support groups for autistic adults. The interview involved one overarching question about their breastfeeding experience. Results: Twenty-three autistic women who breastfed their infant(s) participated in our study. Three main themes were identified including intense sensory perception, focused determination, and one size doesn't fit all . Three subthemes helped to describe intense sensory perception: overstimulated, overtouched, and overwhelmed . Clinical Implications: Autistic adults can have social interaction and expressive communication differences. Nurses can promote positive communication and provide appropriate care through supportive action. These findings offer a guide for nurses to better understand the experiences of autistic breastfeeding women. Abstract : It is estimated that over 1.8 million adult women in the United States have Autism Spectrum Disorder, yet little is known about their childbirth, breastfeeding, and parenting experiences. In this study, autistic women were recruited via social media and invited to share their stories about breastfeeding. Many descrbed being over-stimulated and over-touched, but intensely focused on achieving their breastfeeding goals. Nurses can use these findings in planning care for this subset of childbearing women.